Modelo auto-regressivo aplicado na simulação de um canal rádio para sinais UWB - Silva, Fábio Alexandre Leal da (2009)
Radio channel models are important tools to help in radio systems projects, leading to their optimization. The proposal of this research is to present a model and respective radio channel simulation for ultra wideband (UWB) signals. The UWB technology stands out due to its spectral mask regulation, already emitted by regulation agencies of countries like the United States. The radio channel modeling presented in this work is obtained by a second order autoregressive model whose parameters are calculated through the data processed from frequency domain measurements of the radio channel, for an indoor environment with line of sight between transmitter and receiver. Based on the set of values acquired for the parameters of the second order autoregressive models, three methods are proposed to implement channel models, following a descending order of complexity, which characterization of random parameters is obtained by means of maximum entropy principle. Channel simulation results for the three models are compared to the real channel, adopting the autoregressive model parameters and the time dispersion parameters of the channel (coherence band and delay spread). The results are discussed in order to present more adequate models to represent the radio channel of the environment under analysis.